Glycomics and Proteomics Approaches to Investigate Early Adenovirus–Host Cell Interactions. Issue 13 (22nd June 2018) - Lasswitz, Lisa; Chandra, Naresh; Arnberg, Niklas; Gerold, Gisa
Abstract: Adenoviruses as most viruses rely on glycan and protein interactions to attach to and enter susceptible host cells. The Adenoviridae family comprises more than 80 human types and they differ in their attachment factor and receptor usage, which likely contributes to the diverse tropism of the different types. In the past years, methods to systematically identify glycan and protein interactions have advanced. In particular sensitivity, speed and coverage of mass spectrometric analyses allow for high-throughput identification of glycans and peptides separated by liquid chromatography. Also, developments in glycan microarray technologies have led to targeted, high-throughput screening and identification of glycan-based receptors. The mapping of cell surface interactions of the diverse adenovirus types has implications for cell, tissue, and species tropism as well as drug development. Here we review known adenovirus interactions with glycan- and protein-based receptors, as well as glycomics and proteomics strategies to identify yet elusive virus receptors and attachment factors. We finally discuss challenges, bottlenecks, and future research directions in the field of non-enveloped virus entry into host cells. Graphical abstract: Unlabelled Image Highlights: Adenovirus entry into cells is guided by specific glycan and protein interactions. Glycan arrays and shotgun glycomics methods are valuable technologies to identify virus–glycan interactions. Shotgun proteomics and ligand-based receptor capture are powerful methods for proteinaceous receptor discovery. A combination of shotgun glycomics and proteomics with CRISPR/Cas9 and RNAi validation holds the promise of generating a systems biology view of virus entry processes.